"'The Scientific Method' Doesn't Leave you". Issue 1 (3rd February 2021) - Harkness, Timandra
Abstract: Timandra Harkness interviews Trevor Phillips, the former head of the UK's Commission for Racial Equality and the Equality and Human Rights Commission, about Covid-19 disparities, ethnic identities and origins, and the often fraught relationship between science and politics